Non-local boundary value problem for a system of fractional partial differential equations of the type I - Murat O. Mamchuev (AIMS Mathematics, 2020)
A non-local boundary value problem in a rectangular domain for a system of fractional partial differential equations is investigated, in the case when all the eigenvalues of the matrix coefficient in the main part are sign-definite. Conditions for unique solvability of the problem under studying are obtained.